Pengaruh Pengetahuan dan Perceived Behavior Control terhadap Niat Laki-Laki yang Berhubungan Seksual dengan Laki-Laki (LSL) untuk Melakukan VCT di Kabupaten Madiun - Lestari, Heni Eka; Shaluhiyah, Zahroh; Demartoto, Argyo (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2015)
ABSTRACTEffect of Perceived Knowledge and Behavior Control Of Intention Men having sex with Men (MSM) For Doing VCT In Madiun; MSM realize that risky sexual behavior that they do so may cause transmission of HIV and AIDS, but there is a dilemma that prevents them from doing VCT. This study was conducted to determine the effect of knowledge and perceived behavioral control on intention MSM for VCT. This research is survey explanatory research with cross sectional approach with a large sample of 170 LSL. Bivariate analysis using chi square test and multivariate analysis using logistic regression. The results showed that 53.53% of respondents have the intention to do VCT. Results of bivariate test variables associated with intention MSM VCT is perceived behavior control of the VCT and MSM knowledge about HIV / AIDS and VCT. To improve the intention MSM VCT Madiun district KPA should improve IEC in the MSM community and provide mobile VCT services.Keywords: Men who have sex with men (MSM), the intention VCT, HIV/AIDS